Pengaruh Komunikasi Efektif Terhadap Kualitas Pelayanan Publik Terpadu Satu Pintu Di Dinas Kesehatan Kota Sukabumi - Muhammad Tanziil Suherman (Jurnalika : Jurnal Ilmu Komunikasi, 2023)
The main problem in this research lies in the quality of service, which according to the researcher's initial observations is caused by the ineffectiveness of the communication and information system. Based on the above reflections and considerations, the researcher intends to examine further in the form of dissertation research with the title "The Impact of Effective Information and Communication Systems on Service Quality". The method in this research uses a quantitative approach using a questionnaire instrument according to the characteristics of the data used, this research uses quantitative research methods The method used is a quantitative method based on positivistic philosophy using populations / samples in certain populations / samples and sample collection techniques are carried out randomly. The analysis technique used uses descriptive statistical techniques which function to classify data, analyze, conclude, explain and present the results of its processing.